2019
DOI: 10.1111/jerd.12555
|View full text |Cite
|
Sign up to set email alerts
|

Effects of manufacturing methods on the survival rate of ceramic and indirect composite restorations: A systematic review and meta‐analysis

Abstract: Objectives To evaluate the survival rate of ceramic and indirect composite inlays, onlays, and overlays manufactured according to different methods (CAD/CAM, pressable, and stratified). MEDLINE, EMBASE, and Cochrane Library databases were searched for published articles. Risk of bias, data extraction, subgroup analysis, meta‐analysis, and GRADE was performed. Materials and methods Prospective, retrospective, or RCT studies, without restriction of language, from 1983 to 2019, with follow‐up ≥5 years, reporting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 38 publications
(134 reference statements)
2
19
0
4
Order By: Relevance
“…Similar data were found for survival rates of full crowns, estimated 5-year survival rate for leucite or lithium-disilicate reinforced glass ceramic (96.6%) and sintered alumina and zirconia (96%) were similar [16]. For partial restorations, our results are also in agreement with the literature, Sampaio FBWR et al found estimated survival rates for CAD/CAM of 97% after five years [49].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar data were found for survival rates of full crowns, estimated 5-year survival rate for leucite or lithium-disilicate reinforced glass ceramic (96.6%) and sintered alumina and zirconia (96%) were similar [16]. For partial restorations, our results are also in agreement with the literature, Sampaio FBWR et al found estimated survival rates for CAD/CAM of 97% after five years [49].…”
Section: Discussionsupporting
confidence: 91%
“…Previous reviews on resins were inconclusive whether longevity and survival rates of resins are higher compared to ceramics [55]. However, a recent review on CAD/CAM materials for full and partial crowns that included resin-matrix ceramic showed an estimated survival rate after five years of 82.5% [47,49].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, similar data were obtained in different investigations in which ceramic restorations yielded an 88.7% success rate at 10 years, while composite resins presented a success rate of 84.78% at five years of follow-up [ 30 , 70 ]. Although some articles have concluded that there is little evidence regarding the superior performance of ceramic materials versus composites as onlay restoration materials over the short term, it should be noted that the review was limited to the comparison of only two studies [ 1 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…On analyzing the reasons for restoration failure, fracture (4%) was seen to be the most important cause of failure. Previous studies already identified fracture as the most common cause of failure [ 21 , 42 ]. This could be due to the fact that most of the analyzed studies used ceramic materials, which are known to be particularly prone to fracture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation